Internal polymer pore functionalization through coated particle templating affords fluorine-free green functional textiles. Issue 39 (20th September 2016) - Stucki, M.; Kellenberger, C. R.; Loepfe, M.; Stark, W. J.
Abstract : Green, fluorine-free and fully porous functional membranes were prepared from coated limestone particles in an elastomer at m 2 scales. Abstract : Outdoor clothing traditionally contains large numbers of fluorinated organic compounds to provide water vapour permeability (breathability) and protection against rain water. Persistence and bioaccumulation of such chemicals, however, have resulted in their partial ban (Stockholm protocol by the United Nations, 2009). In this study, we show how a simple pore inside coating provides polymer membranes from stearic acid, limestone and elastomers. The selective coating of a pore's inside is based on first providing a core/shell limestone particle, its incorporation into the elastomer, and subsequent dissolution of the limestone core through dilute acid, leaving the former shell within the polymer pore. The process is transferred to a continuous roll-to-roll coating pilot machine, manufacturing at the m 2 scale. The produced membrane is laminated to a textile, and finally tailored into a functional outdoor jacket. The process demonstrated here to selectively alter pore surfaces serves as a platform membrane technology that is broadly applicable to other polymers and provides a new way to membrane manufacturing.